2021
DOI: 10.1007/s10717-021-00336-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase Composition and Physico-Mechanical Properties at Different Firing Temperatures of Ceramic Earthquake-Resistant Bricks with the Use of Ferro-Dust

Abstract: Ceramic bricks based on low-melting clay and ferro-dust from self-disintegrating, low-carbon, ferrochrome slags, graded from M100 to M175, respectively, were obtained in the temperature range 950 -1100°C. The highest grades are in bricks fired at the temperatures 1050 and 1100°C, respectively, M150 and M175, which can be used as earthquake-resistant. Studies have shown that hematite, wollastonite, diopside and a liquid phase appear at brick firing temperature 950°C. Raising the firing temperature to 1000°C con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…After sintering, a new crystalline Ca-feldspar substance (Figure 3a,b) appeared in the insulation brick, and this was because SiO 2 and Al 2 O 3 in gangue, K-feldspar and fly ash melted into the glassy phase under high temperatures, reacting with CaO and producing Ca-feldspar. Ca-feldspar is a kind of plagioclase with a molecular formula of CaAl 2 Si 2 O 8 , and it generally exists in nonmetallic stable phases [26]. The SEM-EDS image of K15-Ca10 treatment (Figure 4) showed that four elements, Si, Al, O and Ca, are located basically in the same position, which further supports the existence of Ca-feldspar.…”
Section: K-feldspar Promotes the Conversion Of Caco 3 To Ca-feldsparmentioning
confidence: 66%
“…After sintering, a new crystalline Ca-feldspar substance (Figure 3a,b) appeared in the insulation brick, and this was because SiO 2 and Al 2 O 3 in gangue, K-feldspar and fly ash melted into the glassy phase under high temperatures, reacting with CaO and producing Ca-feldspar. Ca-feldspar is a kind of plagioclase with a molecular formula of CaAl 2 Si 2 O 8 , and it generally exists in nonmetallic stable phases [26]. The SEM-EDS image of K15-Ca10 treatment (Figure 4) showed that four elements, Si, Al, O and Ca, are located basically in the same position, which further supports the existence of Ca-feldspar.…”
Section: K-feldspar Promotes the Conversion Of Caco 3 To Ca-feldsparmentioning
confidence: 66%